Ocean acidification along the 24.5°N section in the subtropical North Atlantic. Issue 2 (23rd January 2015) - Guallart, Elisa F.; Fajar, Noelia M.; Padín, Xose Antonio; Vázquez‐Rodríguez, Marcos; Calvo, Eva; Ríos, Aida F.; Hernández‐Guerra, Alonso; Pelejero, Carles; Pérez, Fiz F.
Abstract Ocean acidification is directly related to increasing atmospheric CO2 levels due to human activities and the active role of the global ocean in absorbing part of this anthropogenic CO2. Here we present an assessment of the pH changes that have occurred along 24.5°N in the subtropical North Atlantic through comparison of pH observations conducted in 1992 and 2011. It reveals an overall decline in pH values in the first 1000 dbar of the water column. The deconvolution of the temporal pH differences into anthropogenic and nonanthropogenic components reveals that natural variability, mostly owed to a decrease in oxygen levels in particular regions of the section, explains the vertical distribution of the larger pH decreases (up to −0.05 pH units), which are found within the permanent thermocline. The detection of long‐term trends in dissolved oxygen in the studied region gains importance for future pH projections, as these changes modulate the anthropogenically derived acidification. The anthropogenic forcing explains significant acidification deeper than 1000 dbar in the western basin, within the Deep Western Boundary Current.